Role of platelet-derived growth factor c on endothelial dysfunction in cardiovascular diseases - Grismaldo, Adriana; Sobrevia, Luis [UNESP]; Morales, Ludis (Elsevier, 2022)
Loss of endothelial function is a common feature to all cardiovascular diseases (CVDs). One of the risk factors associated with the development of CVDs is the hyperglycaemia that occurs in patients with metabolic disorders such as Type 1 and Type 2 diabetes mellitus. Hyperglycaemia causes endothelial dysfunction through increased production of reactive oxygen species (ROS) from different cellular sources leading to oxidative stress. Vascular endothelial growth factor (VEGF) is essential in the stimulation and maintenance of endothelial functional aspects and, although it can mitigate the impact of ROS, VEGF-mediated signalling is partially inhibited in diabetes mellitus. The search for therapeutic strategies that preserve, protect and improve the functions of the endothelium is of great relevance in the investigation of CVDs associated with hyperglycaemia. Platelet-derived growth factor C (PDGF-C) is a peptide with angiogenic properties, independent of VEGF, that stimulates angiogenesis and revascularization of ischemic tissue. In a diabetic mouse model, PDGF-C stimulates mature endothelial cell migration, angiogenesis, endothelial progenitor cell mobilization, and increased neovascularization, and protects blood vessels in a retinal degeneration model activating anti-apoptosis and proliferation signalling pathways in endothelial cells. This review summarizes the information on the damage that high D-glucose causes on endothelial function and the beneficial effects that PDGF-CC could exert in this condition.
Keywords: Angiogenesis; Cardiovascular diseases; Diabetes mellitus; High glucose; Platelet-derived growth factor C